Depth-resolved analysis of lattice distortions in high-Ge-content SiGe/compositionally graded SiGe films using nanobeam x-ray diffraction. (25th October 2018) - Shida, Kazuki; Takeuchi, Shotaro; Tohei, Tetsuya; Imai, Yasuhiko; Kimura, Shigeru; Schulze, Andreas; Caymax, Matty; Sakai, Akira
Abstract: We have investigated the three-dimensional configuration of lattice distortions, including lattice plane tilt and twist, in a high-Ge-content constant-composition Si0.3 Ge0.7 (CC-SG)/compositionally graded SiGe strain-relaxed buffer (graded SRB)/Si(001) stacked structure. Position-dependent ω –2 θ – φ mapping (or three-dimensional reciprocal space mapping) by synchrotron-based nanobeam x-ray diffraction revealed the in-plane distributions of both local tilt and twist within an area of 10 × 10 μ m on the sample surface. Depth-resolved crystal information was extracted analytically on the basis of structural features in the graded SRB layer. As a result, a series of tomographic maps that show the three-dimensional distributions of tilt and twist around the CC-SG/graded SRB interface were obtained. Tomographic analysis indicates that the orientation of lattice planes in the graded SRB abruptly changes at a specific depth and at a specific interval. The misfit dislocation distribution observed using transmission electron microscopy is not homogeneous but concentrated at a specific depth, which accounts for the abrupt changes of lattice plane tilt and twist. Our tomographic results clearly verify the dislocation morphology in the SiGe stacked structure, which demonstrates that this analysis method can be a powerful tool for quantitative and non-destructive elucidation of a three-dimensional lattice structure with high spatial resolution.